Yoga for Promoting Physical and Mental Health in Patients with Chronic Kidney Disease: A Systematic Review - Ristanti Puji Astuti; Yustinus Sukarmin; Novita Intan Arovah (Tehran University of Medical Sciences, 2024)
Chronic kidney disease (CKD) is a growing global public health burden with significant physical and mental health challenges. This study aimed to systematically review the available evidence on the effects of yoga interventions on improving the physical and mental health of patients with CKD. The Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines were followed. The systematic search was conducted in January 2023 using Scopus and PubMed, resulting in 99 documents, of which 9 met the selection criteria. The studies explored the effects of different types of yoga interventions on various health aspects in hemodialysis and CKD patients. The durations ranged from 15 days to 6 months. The types of yoga used varied, including Hatha Yoga, Pranayama, and yoga therapy. Outcome measures included dialysis adequacy, fatigue, insomnia, lipid profile, oxidative stress, renal function, blood pressure, and quality of life. The findings demonstrate the feasibility of the yoga intervention and the positive effects of the intervention on health outcomes, such as improved dialysis adequacy, reduced fatigue and insomnia, better lipid profiles, decreased oxidative stress, enhanced renal function, lowered blood pressure, and improved quality of life. Yoga interventions show promise as a complementary approach for managing CKD. The positive effects observed on multiple health outcomes suggest the potential benefits of incorporating yoga into CKD care. However, further well-designed trials are needed to strengthen the evidence base. Healthcare providers should consider including yoga as part of a comprehensive approach to improve the well-being of CKD patients.